Energy Evaluation and Processing Cost Reduction in Agudu Maize Processing Industry - I.J Agabi; J.S Ibrahim (International Journal of Engineering and Management Research, 2021)
This study evaluated energy consumption by Agudu Farms Limited (AFL) that processes maize and cassava into flour for human consumption. The objectives of study included to determine energy contribution to processing cost, to minimize the processing cost and to propose a new selling price per unit of sale of the product. The study materials included; a multi-meter, stopwatch, electrical appliances’ nameplates and bills, fuel purchased receipts, and production records. Data was collected through detailed energy audits and measurements of present electricity consumption. This data was converted into energy intensities, rates and costs, and analyzed. The monthly energy intensity plotted on bar charts using Microsoft excel and the results showed that diesel had the highest consumption variation of 3500 kWh/t, electricity 200kWh/t and labor 110 kWh/t. The percentage of energy contribution to processing cost was 33%. In monetary terms, the processing cost per hour of operation showed average value of ₦830. Whereas, the minimum production cost per hour using Tora software showed ₦767. The new product price per ten-kilogram (10kg) unit of sale of maize flour, using break-even analysis, showed ₦2864. The study observed that diesel contributed more to production cost than electricity and labor and therefore, recommended the setting up of an energy monitoring team to monitor procurement and control utilization of diesel to reduce production cost.